The influence of air pollution on the phyllosphere microflora composition of Tillandsia leaves (BromeHaceae) - Brighigna, Luigi (Universidad de Costa Rica, 2000)
The effect of air pollution on total phyllospheric microflora from two species of the epiphytic neo tropical genus Tillandsia (Bromeliaceae) was studied by comparing unpolluted plants living in a forest (Escazú, San José) with polluted ones from an urban site of Costa Rica (San José city). Dilutions of homogenized leaf samples were plated on media suitable for each microbial group. For each microorganism group, total counts were performed and purified strains of randomly chosen colonies were identified. There was a global reduction in the number of living microorganisms due to pollution effects, especially yeasts and bacteria, while nitro gen-fixing microorganisms and fungi were les s affected. Our results showed that the phyllosphere microflora of Tillandsia plants living in a tropical urban environment changes in terms of number and species composition of yeasts and bacteria with respect to plants living in unpolluted environment.